TINGKAT LITERASI MAHASISWA FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI JAKARTA TERHADAP MEDIA DAN INFORMASI (MEDIA AND INFORMATION LITERACY) - Lussy Dwiutami Wahyuni; Evita Adnan (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2009)
University students should have ability in media and information literacy. Media and information literacy is skill to access, analyze, evaluate, and communicate information in several forms. Students know and understand information comprehensively to make up critical thingking : to analyze and evaluate the information. This research want to know about how is university student’s media and information literacy.